An Empirical Assessment of Organizational Commitment Using the Side-Bet Theory Approach - Cohen, Aaron; Gattiker, Urs E. (Relations industrielles / Industrial Relations, 1992)
According to the side-bet theory, organizational commitment increases with the accumulation of side bets or investments. Cross-national data for 7 side-bet indexes (age, tenure, education, marital status, salary, gender, and hierarchical position) were used to test the theory's generalizability. Four hundred and sixty-three white-collar employees in Canada and the US were surveyed. The findings indicate that while organizational commitment levels between Canadian and US respondents were similar, the effects of various side-bet indexes differed between the 2 countries. The results suggest that previously reported correlations between age, tenure and organizational commitment cannot be replicated.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Commitments; Corporate loyalty; Employee attitude; Labor Unions; Organizational behavior; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Statistical analysis; Studies; Variables